Employee Engagement Measurement which Affecting Turnover at ABC Banking Company - M. Archam Ubaidillah; Bambang Syairudin; Indung Sudarso (Institut Teknologi Sepuluh Nopember, 2019)
In 2017, there were 84 employees had voluntarily quit in ABC bank indicating 1.90% turnover ratio. This number was the highest record for the last 4 years, and almost reaching the maximum allowed limit (2.00%). This turnover resulted financial loss for the company, therefore the number must be reduced. Some research in the past found low engagement level allowed an employee to have an intention to quit. This research purpose was to reveal the most dominant factor affecting the employee engagement. The object of this research was the staff-level permanent employee of ABC bank, situated in central office Surabaya. Employee engagement construct was formed from job and organization engagement factors, with seven antecedent factors (job characteristic, perceived organizational support, perceived supervisor support, coworker relations, rewards and recognition, organizational justice and self-consciousness), and the intention to quit as the consequence factor. From 266 participants found 37.22% were disengaged, and 72.73% of them had an intention to quit. The model analysis implied that perceived supervisor support had a highest influence on engagement, and consequently effecting the intention to quit. This research concluded that supervisor role improvement is required to support human resource strategy to achieve the competitive advantage